Development Strategy for Tangkup Waterfall Towards Sustainable Tourism - KRISNA, Ary; CITRA, Dewi; JANUARIANTA, Januarianta; AMERTHA, Sahya; WIWEKA, Darma; LAKSMI, Putu Ayu Sita (PT Batara Swastika Harati, 2024)
This community service project, a collaborative effort between the government, the local community, and the tourism awareness groups, aims to provide development strategies for achieving sustainable tourism in Undisan Village. The main focus of the initiative is on our collective roles as facilitators, regulators, and motivators in supporting the Sustainable Development Goals (SDGs) in the area. The primary issue identified is the unsustainable economic development of the local community. The optimal utilization of Tangkup Waterfall in Undisan Village as a tourist destination is also a key concern. The results of this community service project indicate that the government, local community, and tourism awareness groups play a crucial role as facilitators in improving the supporting infrastructure and facilities for tourism in Undisan Village. As regulators, the government is responsible for designing regulations and policies that support sustainable tourism management. However, the government's role as a motivator has yet to be fully realized, necessitating efforts in socialization, training, and allocating stimulant funds to further develop tourism management in the area. In conclusion, the government has a strategic role in achieving the SDGs in Undisan Village through sustainable tourism development. Implementing strategies that align with the region's needs and potential is expected to make positive contributions to the economic, ecological, and socio-cultural aspects.